Synthesis and immunological properties of conjugates composed of group B streptococcus type III capsular polysaccharide covalently bound to tetanus toxoid. - Lagergard, T (1990)
A synthetic scheme for covalently binding group B streptococcus type III to tetanus toxoid (TT), using adipic acid dihydrazide as a spacer, is described. Type III alone or as a conjugate with TT was injected subcutaneously into laboratory mice, and the type-specific and TT antibody responses elicited by these immunogens were assayed. Type III-TT elicited significantly higher levels of type-specific antibodies after each immunization than did the type III alone. These levels were related to the dosage of the conjugate, enhanced by Freund adjuvant, and exhibited booster responses. Type III alone elicited only immunoglobulin M (IgM) antibodies in Swiss albino mice and mostly IgM and low levels of IgG antibodies of the IgG3 subclass in BALB/c mice. Type III-TT conjugates, in contrast, elicited mostly IgG antibodies in both strains of mice. IgA type III antibodies were not detected. The first two immunizations with the conjugates elicited type III antibodies in the IgG1 and in the IgG3 subclasses. Low levels of IgG2a type III antibodies were detected after a third injection of type III-TT. Conjugate-induced antibodies facilitated opsonization of group B streptococcus type III organisms and did not react with the structurally related pneumococcus type 14. TT alone or as a component of type III-TT induced mostly antibodies of the IgG class: IgG1 levels were the highest of the four subclasses. No IgA TT antibodies were detected. The conjugation procedure, therefore, enhanced the immunogenicity of and conferred T-cell dependent properties to the type III while preserving the immunogenicity of the TT component. The T-cell dependent properties of the conjugates were responsible for stimulating IgG type III antibodies which could be boosted. Evaluation of type III-TT conjugates in antibody-negative women of child-bearing age is planned.